Softening processes research when demineralizing mine water with anionite AV-17-8 - Кучерик, Галина Валентинівна; Омельчук, Юлія Аркадіївна; Гомеля, Микола Дмитрович (Eastern-European Journal of Enterprise Technologies, 2013)
The basic task of the study of softening processes when demineralizing mine water with an anionite AV-17-8 was softening of mine water with simultaneous recovery of chloride- and sulfate anions. The problem can be solved if to run mine water through the anionite in the main form when softening. That will ensure the recovery of chlorides and sulfates with simultaneous alkalization of water for the account of transition to the solution of anions OH-. Under alkalization of water magnesium ions hydrolyze and remove as a sediment of Mg (OH)2, and calcium ions fall out as carbonates. The consumption of the basic reagents is close to their consumption at reagent water softening. However, in this case not only hardness ions, but also chlorides and sulfates remove out of water. The alkalinity of first samples is quite high. One can use that to reduce source water hardness by blending the source and purified by anionite water. The method can be used when preparing mine water with high salinity, hardness and alkalinity to thermal power systems, cooling systems in industry and power engineering